EFFECTIVENESS OF LEARNING MEDIA BASED ON QUIZIZZ APPLICATION WITH REALISTIC MATHEMATICS EDUCATION APPROACH - Andi Alim Syahri; Gaffar, Abdul; Ma'rup (MATEMATIKA DAN PEMBELAJARAN, 2024)
This study aims to determine the effectiveness of mathematics learning through learning media based on the Quizizz application with the RME Approach for students in class VIII.D SMP Negeri 1 Sungguminasa, this study refers to three learning effectiveness, namely seen from mathematics learning outcomes, student activities, and student responses.  This type of research is a pre-experiment that only involves one class as an experimental class with a One Group Pretest-Posttest Design research design. The experimental class was class VIII.D SMP Negeri 1 Sungguminasa consisting of 38 students. The instruments in this study were tests, observation sheets and questionnaires through Quizizz application-based learning media with the RME Approach. The results showed: 1) Students' mathematics learning outcomes were categorised as "Improved" and "Completed" classically, namely 97.37% of students reached individual completeness t_count=19.953>t_table=1.687, 2) Students' activities in learning mathematics were categorised as "Active" which increased by 78.38%, and 3) Students' response to mathematics learning was categorised as "positive" which was 98.31%. Based on the results of this study. students have met the criteria for the effectiveness of mathematics learning, so it can be concluded that mathematics learning is effectively implemented through Quizizz application-based learning media with the RME Approach for students in class VIII.D SMP Negeri 1 Sungguminasa. Keywords: Effectiveness; Learning Media; Quizizz; RME